Determinants of working capital management before, during and after the global financial crisis of 2008: evidence from Malaysia - Haron, Razali; Mansour Nomran, Naji (2015)
The study aims to investigate the determinants of working capital management (WCM) on a sample of 57 Malaysian firms in three different scenarios of 2008 global financial crisis, before (2002-2006), during (2007-2008) and after the global financial crisis (2009-2012). Six explanatory variables commonly cited were employed to identify variations in cash conversion cycle (CCC) which acts as the measurement for WCM in this study. These variables are profitability, debt, sales growth, free cash flow, firm size and liquidity. By employing pooled OLS and random effect model, it was found that four out of the six explanatory variables have significant relationships with WCM before the crisis. These factors are profitability, debt; sales growth and firm size. It is interesting to note that the same variables have significant relationships with WCM as well after the crisis of 2008. Thus, firms should take note that when dealing with WCM during non-crisis periods, they should give particular attention to profitability, debt; sales growth and firm size. In contrast, it was found that profitability, firm size and free cash flow are significantly affecting WCM during the financial crisis of 2008. With this extra information on the contributing factors to effective WCM of a firm during these three important periods, this study has filled the gap in the body of knowledge and the management can perhaps deal with the situation more effectively and be resilient in whatever economic situations.